Development of Social Science Education Teaching Modules for Character Building by Strengthening the Pancasila Student Profile - Azhari, Azhari; Sumanti, Sumanti; Novalita, Rahmi (Postgraduate School, Universitas Negeri Padang, 2023)
Based on preliminary research conducted in Elementary School (ES) 25 Sawang found many problems in learning social studies including low motivation to learn and monotonous learning and learning resources that only use printed books and student worksheets so that the value becomes low, The purpose of this study is to 1) analyze the characteristics of social studies teaching modules for grade v students 25 Sawang ES. 2) test the validity of social studies teaching modules for grade V ES 25 Sawang. This type of research is Reseach and Developmend (R&D) research with a level of development at the second level, namely existing products and then tested for validity, the development steps using Sugiyono's 2015 development, namely 1) setting certain products in this case the social studies module theme Works for red and white. 2) needs analysis which includes problem analysis, curriculum analysis, student analysis, material analysis. 3) the first trial conducted is the validity test conducted by experts (experts, 4) individual trials, 5) small group trials, 6) test results compared to the standard 7) and conclusions and suggestions. The test subjects were teachers and students of 25 Sawang Primary School. The data were collected using observation, interview, and documentation techniques. The data collection tools used questionnaires, validation sheets, and data analysis tools using SPSS Version 27.